Eva and Baby Mo - Elliott, Rebecca (New York : Scholastic Inc., 2019)
Eva offers to babysit her little brother Baby Mo so her parents can go to a sky-dancing competition, and she enlists a couple of her friends to help, unfortunately Mo proves to be a handful, eating too much candy, making a big mess, and throwing a tantrum, and she and her friends have to clean up fast before her parents get home.
"Branches."
2.7
1-4
Accelerated Reader AR
Keywords: Owls -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Babysitting -- Juvenile fiction; Friendship -- Juvenile fiction; Diaries -- Juvenile fiction; Owls -- Fiction; Brothers and sisters -- Fiction; Babysitters -- Fiction; Friendship -- Fiction; Diaries -- Fiction; Owls -- Fiction; Siblings -- Fiction; Babysitters -- Fiction; Friendship -- Fiction; Diaries -- Fiction